Zebrafish Sebagai Model Hewan Coba Untuk Riset Diabetes - Lim, Anthony Camilo; Rochmanti, Maftuchah; Khotimah, Husnul (Syifa'Medika, 2025)
Diabetes mellitus (DM) is a major global health problem, affecting over 500 million people worldwide. Understanding its pathophysiology and complications requires suitable animal models. Zebrafish (Danio rerio) has emerged as a promising model for diabetes research. This review aims to synthesize current research on the use of zebrafish as an experimental model for DM and its microvascular complications, focusing on induction methods, research applications, and observed outcomes. A literature review was conducted to investigate those variables. Zebrafish hyperglycemia can be induced through glucose immersion, overfeeding, chemical agents, and genetic modification. These models have been successfully used to study drug testing, molecular profiling, and diabetic complications. Observed variables included glucose levels, enzyme activity, gene expression, histopathological changes, and behavioral responses. Results demonstrated strong parallels with human diabetic pathology, including vascular alterations, proteinuria, renal apoptosis, and neuropathic dysfunction. Zebrafish provides a strong, cost-effective, and relevant model for diabetes research. Despite limitations such as physiological differences and methodological variability, they offer valuable insights into metabolic dysregulation and complications, while serving as an efficient platform for drug discovery.